Triple‐negative breast cancer—Role of immunology: A systemic review. Issue 5 (4th December 2019) - Oner, Gizem; Altintas, Sevilay; Canturk, Zafer; Tjalma, Wiebren; Verhoeven, Yannick; Van Berckelaer, Christophe; Berneman, Zwi; Peeters, Marc; Pauwels, Patrick; van Dam, Peter A.
Abstract: Recently, the complex role of immune therapy has been the target of increased attention in breast cancer, particularly in triple‐negative breast cancer (TNBC). Although TNBC is sensitive to chemotherapy, the recurrence and mortality rates are worse compared with the other breast cancer types. In addition, TNBC still lacks targeted treatment options. With the improved understanding of the immune system in TNBC, it is expected that new predictive and prognostic markers will be identified, and innovative treatment modalities will be developed. The aim of this review was to provide an overview of the effector cells in the TNBC's microenvironment and to highlight a novel approach to treat this kind of cancer. A computer‐based literature research was carried out using PubMed, American Society of Clinical Oncology Annual Meeting (ASCO) and San Antonio Breast Cancer Symposium (SABCS). To date, studies have shown that tumor‐infiltrating lymphocytes (TILs) and tumor‐associated macrophages ( TAMs) play a very important role in the TNBC's microenvironment. Tumor‐infiltrating lymphocytes can even be considered as biomarkers to predict chemotherapy response in TNBC. Furthermore, TNBC was shown to have immune active subtypes, and therefore, the use of immunotherapy may be an attractive treatment approach. In this respect, several randomized studies have been designed or are currently ongoing to explore the combination of chemotherapy with immunotherapy in TNBC. Combination of chemo‐ and immunotherapy is likely to be beneficial in a subgroup of patients with TNBC.